Transcatheter aortic “valve-in-valve” for degenerated bioprostheses: Choosing the right TAVI valve - Ferrari, Enrico (Annals of Cardiothoracic Surgery, 2012)
Bioprosthetic aortic valve replacement is the treatment of choice for patients over 65 years of age suffering from aortic valve disease, and for younger patients with contraindications to long-lasting anticoagulation. Despite several technical improvements to reduce the risk of structural valve degeneration (SVD), the risk of SVD still exists, in particular for hemodialysis patients and patients under 60 years of age at surgery. Redo open heart surgery is the treatment of choice in case of valve degeneration, but caries a higher surgical risk when elderly patients with comorbidities are concerned. In the last 5 years, transcatheter aortic “valve-in-valve” procedures represent a valid alternative to standard redo surgery in selected patients. Valve-in-valve procedures represent a less invasive approach in high-risk patients and the published results are very encouraging. Technical success rates of 100% have been reported, as have the absence of paravalvular leaks, acceptable trans-valvular gradients (depending on the size of the original bioprosthesis), and low complication rates. The current article focuses on choosing the correct transcutaneous valve to match the patient’s existing bioprosthesis for valve-in-valve procedures.